2006
DOI: 10.1111/j.1365-2117.2006.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Miocene to Recent exhumation of the central Himalaya determined from combined detrital zircon fission‐track and U/Pb analysis of Siwalik sediments, western Nepal

Abstract: Fission-track (FT) analysis of detrital zircon from synorogenic sediment is a well established tool to examine the cooling and exhumation history of convergent mountain belts, but has so far not been used to determine the long-term evolution of the central Himalaya. This study presents FT analysis of detrital zircon from 22 sandstone and modern sediment samples that were collected along three stratigraphic sections within the Miocene to Pliocene Siwalik Group, and from modern rivers, in western and central Nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
180
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(201 citation statements)
references
References 101 publications
(258 reference statements)
19
180
2
Order By: Relevance
“…The single-grain track counts are used as input data and an automatic peak-fitting procedure calculates the peak age and confidence intervals for age components that fit the measured data. Because those age populations and their peak ages are commonly reported and used for the geological interpretation in detrital thermochronometric studies (e.g., Brandon et al, 1998;Garver et al, 2005;Bernet et al, 2006Bernet et al, , 2009Enkelmann et al, 2009Enkelmann et al, , 2011Falkowski et al, 2014), we investigate here the effect of various sampling approaches on the peak fitting results. The peak age and the 1σ confidence interval are given, as well as the relative size of the population with respect to the entire number of grains measured per sample (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-grain track counts are used as input data and an automatic peak-fitting procedure calculates the peak age and confidence intervals for age components that fit the measured data. Because those age populations and their peak ages are commonly reported and used for the geological interpretation in detrital thermochronometric studies (e.g., Brandon et al, 1998;Garver et al, 2005;Bernet et al, 2006Bernet et al, , 2009Enkelmann et al, 2009Enkelmann et al, , 2011Falkowski et al, 2014), we investigate here the effect of various sampling approaches on the peak fitting results. The peak age and the 1σ confidence interval are given, as well as the relative size of the population with respect to the entire number of grains measured per sample (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a detrital sample, the youngest age population found in the measured age distribution of a sample provides information about the fastest rock cooling in the catchment and is commonly used for assessing maximum exhumation rates that can be compared to other catchments in the region, or to earlier or later deposits within a stratigraphic section (Fig. 3) (e.g., Bernet et al, 2006Bernet et al, , 2009Coutand et al, 2006;Enkelmann et al, 2011;Tranel et al, 2011). Older age populations found in the age distribution refer to earlier stages of cooling and either originate from higher elevations in the catchment, the less rapidly exhumed rock in a catchment of differential denudation (e.g., due to faulting; Whipp et al, 2009), older and unreset sedimentary strata, or reworked sediments (e.g., Garver et al, 1999Garver et al, , 2005Perry et al, 2009).…”
Section: Thermochronologymentioning
confidence: 99%
“…Deeken et al (2011) used zircon (U-Th/He) thermochronometric data to argue for uplift ∼100 km west of the westernmost exposure of the oLH via active thrusting on faults to the south of the MCT by at least ∼15 Ma, which is supported by data presented herein. Similarly, Bernet et al (2006) propose LH exhumation in the Nepali Himalaya around ∼16 Ma. They postulate that uplift and erosion at this time led to widespread cooling, as recorded by zircon fission track ages, due to movement along the STFS, MCT, and the Ramgarh Fault, the latter of which includes iLH-equivalent rocks in its hanging wall.…”
Section: Evidence For ∼16 Ma Exhumation Of the Upper Lh Succession Anmentioning
confidence: 96%
“…The timing of the final unroofing of the Greater Himalaya is also poorly defined Bernet et al, 2006;Najman, 2006;Szulc et al, 2006) and should be indicated by influxes of high-grade metamorphic minerals into the Indus Fan. Seeing whether the arrival of this material from the Greater Himalaya coincides with, or likely follows, intensification of the summer monsoon rains would be a critical test of the channel flow and competing orogenic wedge models.…”
Section: Reconstruct Changes In Erosion and Weathering Intensity Overmentioning
confidence: 99%